Treatment of giant fecalith colonic obstruction in a patient with Duchenne muscular dystrophy using endoscopic injection of hydrogen peroxide: a case report and literature review - Huang, Cheng; Gao, Zhichao; Zhang, Yuhang; Li, Guofeng; Ge, Lida (Frontiers in Medicine, 2024)
Introduction Duchenne muscular dystrophy (DMD) is an X-linked recessive genetic disorder primarily affecting cardiac and skeletal muscles, with gastrointestinal obstruction being an infrequent complication. Case report We present a 17-year-old boy with DMD (G-to-T transversion at c.4150 in the gene encoding dystrophin protein) who developed severe colonic obstruction due to fecal impaction. Abdominal computed tomography revealed an obstructing fecalith in the left colon (length: 39.5 cm, width: 18.3 cm, height: 12.7 cm). Despite the application of initial conservative measures including fasting, enemas, and fluid resuscitation, the obstruction persisted. Therefore, we performed manual disimpaction and endoscopic injection of hydrogen peroxide, effectively alleviating the obstruction. Discussion This case underscores the necessity of devising stage-specific, tailored strategies for the prevention and management of gastrointestinal complications in patients with DMD.